Copper homeostasis in Streptococcus and Neisseria: Known knowns and unknown knowns - Howell, Archie; Chogule, Safa; Djoko, Karrera Y. (Advances in microbial physiology, 2025)
Our research group studies copper (Cu) homeostasis in Streptococcus and Neisseria, with a current focus on species that colonise the human oral cavity. Our early ventures into this field very quickly revealed major differences between well-characterised Cu homeostasis systems in species with well-known pathogenic potential and the uncharacterised systems in species that are considered as components of the normal healthy human microflora. In this article, we summarise the known and predicted mechanisms of Cu homeostasis in Streptococcus and Neisseria. We focus exclusively on proteins that directly sense and change (increase or decrease) cellular Cu availability. Where relevant, we make comparisons with examples from species isolated from outside the human oral cavity and from animal hosts. The emerging picture depicts diverse cellular strategies for handling Cu, even among closely related bacterial species.